Burn the boats toss plan B overboard and unleash your full potential - Matt Higgins (New York William Morrow, an Imprint of HarperCollins Publishers, 2023)
"Successful serial entrepreneur and Guest Shark on Shark Tank Matt Higgins shows you how to conquer your fears and reach new heights by "burning your boats"-throw away your Plan B, removing any chance for an exit, and you have no choice but to win"-- Provided by publisher.
Keywords: Risk